The influence of Sb doping on the local structure and disorder in thermoelectric ZnO:Sb thin films - Ribeiro, Joana M.; Rodrigues, Frederico J.; Correia, Filipe C.; Pudza, Inga; Kuzmin, Alexei; Kalinko, Aleksandr; Welter, Edmund; Barradas, Nuno P.; Alves, Eduardo; LaGrow, Alec P.; Bondarchuk, Oleksandr; Welle, Alexander; et al. (Elsevier, 2023)
Thermoelectric transparent ZnO:Sb thin films were deposited by magnetron sputtering, with Sb content varying between 2 and 14 at%. As evidenced by X-ray diffraction analysis, the films crystallize in the ZnO wurtzite structure for lower levels of Sb-doping, developing a degree of amorphization for higher levels of Sb-doping. Temperature-dependent (10–300 K) X-ray absorption spectroscopy studies of the produced thin films were performed at the Zn and Sb K-edges to shed light on the influence of Sb doping on the local atomic structure and disorder in the ZnO:Sb thin films. The analysis of the Zn K-edge EXAFS spectra by the reverse Monte Carlo method allowed to extract detailed and accurate structural information in terms of the radial and bond angle distribution functions. The obtained results suggest that the introduction of antimony to the ZnO matrix promotes static disorder, which leads to partial amorphization with very small crystallites (∼3 nm) for large (12–14 at%) Sb content. Rutherford backscattering spectrometry (RBS) experiments enabled the determination of the in-depth atomic composition profiles of the films. The film composition at the surfaces determined by X-ray photoelectron spectroscopy (XPS) matches that of the bulk determined by RBS, except for higher Sb-doping in ZnO films, where the concentration of oxygen determined by XPS is smaller near the surface, possibly due to the formation of oxygen vacancies that lead to an increase in electrical conductivity. Traces of Sb–Sb metal bonds were found by XPS for the sample with the highest level of Sb-doping. Time-of-flight secondary ion mass spectrometry obtained an Sb/Zn ratio that follows that of the film bulk determined by RBS, although Sb is not always homogeneous, with samples with smaller Sb content (2 and 4 at% of Sb) showing a larger Sb content closer to the film/substrate interface. From the optical transmittance and reflectance curves, it was determined that the films with the lower amount of Sb doping have larger optical band-gaps, in the range of 2.9–3.2 eV, while the partially amorphous films with higher Sb content have smaller band-gaps in the range of 1.6–2.1 eV. Albeit the short-range crystalline order (∼3 nm), the film with 12 at% of Sb has the highest absolute Seebeck coefficient (∼56 μV/K) and a corresponding thermoelectric power factor of ∼0.2 μW·K−2·m−1. --//-- This is an open access article Joana M. Ribeiro, Frederico J. Rodrigues, Filipe C. Correia, Inga Pudza, Alexei Kuzmin, Aleksandr Kalinko, Edmund Welter, Nuno P. Barradas, Eduardo Alves, Alec P. LaGrow, Oleksandr Bondarchuk, Alexander Welle, Ahmad Telfah, Carlos J. Tavares, "The influence of Sb doping on the local structure and disorder in thermoelectric ZnO:Sb thin films", Journal of Alloys and Compounds, Volume 939, 2023, 168751, ISSN 0925-8388, https://doi.org/10.1016/j.jallcom.2023.168751 published under the CC BY licence.
The experiment at HASYLAB/DESY was performed within the project I-20200161 EC. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01–2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. This work was carried out in part through the use of the INL Advanced Electron Microscopy, Imaging and Spectroscopy Facility. This work (proposal ID 2018–020-022469) was carried out with the support of the Karlsruhe Nano Micro Facility (KNMFi, www.knmf.kit.edu), a Helmholtz Research Infrastructure at Karlsruhe Institute of Technology (KIT, www.kit.edu). Joana Ribeiro is grateful to the Fundação para a Ciência e Tecnologia (FCT, Portugal) for the Ph.D grant SFRH/BD/147221/2019. Filipe Correia is grateful to the FCT, Portugal, for the Ph.D. grant SFRH/BD/111720/2015. The authors also acknowledge the funding from FCT/PIDDAC through the Strategic Funds project reference UIDB/04650/2020–2023.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Antimony; Doped zinc oxide; Thin films; Sputtering; Thermoelectric; X-ray absorption